Aeration-manganese sand filter-ultrafiltration to remove iron and manganese from water: Oxidation effect and fouling behavior of manganese sand coated film. (December 2020) - Cheng, Li-Hua; Xiong, Zhao-Zhao; Cai, Shuo; Li, Du-Wang; Xu, Xin-Hua
Graphical abstract: Highlights: The AMU process can effectively remove Fe 2+ and Mn 2+ from groundwater. Manganese sand coated film increases the redox potential of groundwater. The upper and lower layer of manganese sand coated films are found different. The needle crystals of Fe2 O3 can be found in coated film and membrane fouling. Abstract: High concentration of iron and manganese is still one of the common problems in groundwater. In this work, an integrated aeration-manganese sand filter-ultrafiltration (AMU) process was proposed to investigate the form of iron and manganese oxides and its autocatalytic effect in removing iron and manganese. The pourbaix diagram was used to characterize the degree of iron and manganese oxidation. The dependence of redox potential and atomic composition on manganese sand was then studied. The results showed that the proposed AMU process could not only remove 100 % ferrous and 90 % manganese ions due to the increased redox potential by 2 mV after manganese sand filter, but also reduce the membrane fouling due to the retention effect of manganese sand coated films formed on the surface of manganese sand. The upper layer of manganese sand coated film contained 21.86 wt% Fe whereas the lower layer contained 19.31 wt% Mn compared with that of 13.77 wt% Fe and 4.87 wt% Mn for the virgin one, respectively. The needle crystals Fe2 O3 and unshaped crystals MnOx found on both the manganese sand coated films and membrane foulants indicated the anti-fouling effect of ultrafiltration membrane through the complete oxidation of iron and manganese. The proposed AMU process allowed the simultaneous oxidation and the following membrane fouling mitigation of the whole process for iron and manganese removal from groundwater.